Lithium Storage Performance Boosted via Delocalizing Charge in ZnxCo1−xPS3/CoS2 of 2D/3D Heterostructure - Zhong, Hou‐Yang; Lu, Xian; Zhong, Yu; Zhao, Yi; Liu, Xin‐Ming; Cheng, Dan‐Hong; Huang, Xiao‐Ying; Du, Ke‐Zhao; Wu, Xiao‐Hui (Small (Weinheim an der Bergstrasse, Germany), 2022)
A promising anode material consisting of bimetallic thiophosphate ZnxCo1−xPS3 and CoS2 with 2D/3D heterostructure is designed and prepared by an effective chemical transformation. Density functional theory calculations illustrate that the Zn2+ can effectively modulate the electrical ordering of ZnxCo1−xPS3 on the nanoscale: the reduced charge distribution emerging around the Zn ions can enhance the local built‐in electric field, which will accelerate the ions migration rate by Coulomb forces and provide tempting opportunities for manipulating Li+ storage behavior. Moreover, the merits of the large planar size enable ZnxCo1–xPS3 to provide abundant anchoring sites for metallic CoS2 nanocubes, generating a 2D/3D heterostructure with a strong electric field. The resultant ZnxCo1−xPS3/CoS2 can offer the combined advantages of bimetallic alloying and heterostructure in lithium storage applications, leading to outstanding performance as an anode material for lithium‐ion batteries. Consequently, a high capacity of 794 mA h g−1 can be retained after 100 cycles at 0.2 A g−1. Even at 3.0 A g−1, a satisfactory capacity of 465 mA h g−1 can be delivered. The appealing alloying‐heterostructure and electrochemical performance of this bimetallic thiophosphate demonstrate its great promise for applications in practical rechargeable batteries. A promising anode material consisting of bimetallic thiophosphate ZnxCo1−xPS3 and CoS2 with 2D/3D heterostructure is prepared. The hetero‐Zn alloying can produce an enhanced asymmetric E‐field to accelerate electron transfer and adjust the interlayer distance to create small volume changed MPS3 electrodes. Additionally, metallic CoS2 deposited on semiconductor ZnxCo1−xPS3 can form a strong E‐field, favoring the transportation of electrons.